2010
DOI: 10.1111/j.1365-2966.2010.17713.x
|View full text |Cite
|
Sign up to set email alerts
|

Spectrophotometric distances to Galactic H ii regions

Abstract: We present a near‐infrared study of the stellar content of 35 H ii regions in the Galactic plane, 24 of which have been classified as giant H ii regions. We have selected these optically obscured star‐forming regions from the catalogues of Russeil, Conti & Crowther and Bica et al. In this paper, we have used the near‐infrared domain J‐, H‐ and Ks‐band colour images to visually inspect the sample. Also, we have used colour‐colour and colour–magnitude diagrams to indicate ionizing star candidates, as well as the… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
90
2

Year Published

2012
2012
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 79 publications
(106 citation statements)
references
References 95 publications
(297 reference statements)
14
90
2
Order By: Relevance
“…This is supported by statistical studies; for instance, Battersby et al (2011) show that tracers of star formation are more likely associated with higher dust temperatures, while König et al (2016) show an increase in dust temperature with evolutionary stage by fitting the spectral energy distribution of ATLASGAL clumps over a range of evolutionary stages. Hence, a temperature correction is neces- Sanna et al (2014) (g) Moisés et al (2011) ( †) We revised the spectrophotometric distance of 1.81 kpc by Moisés et al (2011). (h) Wu et al (2014) (i) Wu et al (2012) (j) Reid et al (2014) (k) Dutra et al (2003) (l) Straw et al (1987) (m) Xu et al (2011) (n) Sanna et al (2009) (o) Leurini et al (2011) (p) Kurayama et al (2011) (q) Russeil (2003) (r) Motogi et al (2011) (s) López et al (2011) ( ‡) Peretto et al (2013) adopts 3.25 kpc.…”
Section: Temperature Estimatesmentioning
confidence: 99%
See 1 more Smart Citation
“…This is supported by statistical studies; for instance, Battersby et al (2011) show that tracers of star formation are more likely associated with higher dust temperatures, while König et al (2016) show an increase in dust temperature with evolutionary stage by fitting the spectral energy distribution of ATLASGAL clumps over a range of evolutionary stages. Hence, a temperature correction is neces- Sanna et al (2014) (g) Moisés et al (2011) ( †) We revised the spectrophotometric distance of 1.81 kpc by Moisés et al (2011). (h) Wu et al (2014) (i) Wu et al (2012) (j) Reid et al (2014) (k) Dutra et al (2003) (l) Straw et al (1987) (m) Xu et al (2011) (n) Sanna et al (2009) (o) Leurini et al (2011) (p) Kurayama et al (2011) (q) Russeil (2003) (r) Motogi et al (2011) (s) López et al (2011) ( ‡) Peretto et al (2013) adopts 3.25 kpc.…”
Section: Temperature Estimatesmentioning
confidence: 99%
“…We collected distance estimates from the literature using primarily maser parallax measurements (see Reid et al 2014 for an overview) or spectrophotometric distance estimates (e.g. Russeil 2003;Moisés et al 2011) for the known GMCs. For the remaining unassociated sources we used the high-density tracer NH 3 to determine kinematic distances from Wienen et al (2012Wienen et al ( , 2015.…”
Section: Distances and Association With Massive Molecular Complexesmentioning
confidence: 99%
“…Pinheiro et al (2010) identified the ionizing stars in nine HII regions, and derived their photometric distances. Moisés et al (2011) used the nearinfrared color images to study the stellar content of 35 HII regions, and estimated their spectrophotometric distances. Russeil et al (2012) analyzed the data of OB stars in two star forming complexes (see , NGC 6334 and NGC 6357, and revised their photometric distances.…”
Section: Hii Regionsmentioning
confidence: 99%
“…The kinematic distance ambiguity for many HII regions, GMCs, and 6.7 GHz methanol masers has been solved (e.g., Roman-Duval et Lépine et al 2011;Anderson et al 2012;Urquhart et al 2012;Jones & Dickey 2012), which enables us to estimate their kinematic distances. In addition, the more reliable trigonometric or photometric distances of a number of HII regions or masers have been measured (e.g., Rygl et al 2010;Sato et al 2010a; Moisés et al 2011;Xu et al 2011Xu et al , 2013Russeil et al 2012;Zhang et al 2014;Foster & Brunt 2014). The available spiral tracers have almost doubled as compared to those listed in Hou et al (2009).…”
Section: Introductionmentioning
confidence: 99%
“…Kinematic distances have been determined for 17 of these masers by Green & McClure-Griffiths (2011) 2 , spectrophotometric distances have been determined for 2 masers by Moisés et al (2011) and maser parallax distances are available for another 2 sources (MMB196.454-01.677 and MMB232.620+00.996; Honma et al 2007 andReid et al 2009b, respectively). Combined with the sources associated with complexes, these two steps provide distances for 38 of the 77 methanol masers of interest for this study.…”
Section: Literature Distancesmentioning
confidence: 99%